2022
DOI: 10.1093/pnasnexus/pgac231
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic activation of a family of TetR type transcriptional regulators controls phenotypic heterogeneity in Acinetobacter baumannii

Abstract: Phenotypic heterogeneity is an important mechanism for regulating bacterial virulence, where a single regulatory switch is typically activated to generate virulent and avirulent subpopulations. The opportunistic pathogen Acinetobacter baumannii can transition at high frequency between virulent opaque (VIR-O) and avirulent translucent (AV-T) subpopulations, distinguished by cells that form opaque or translucent colonies. We demonstrate that expression of eleven TetR-type transcriptional regulators (TTTRs) can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Tetracycline resistance is typically acquired through the activation of efflux pumps ( 18 , 19 ). The family of TetR-type transcriptional regulators is redundantly involved in driving this switching through uncharacterized molecular events ( 3 , 6 ). Strain AB5075 does not possess intrinsic resistance to tetracycline due to the absence of the tetRA cassette ( 20 ), despite having multiple copies of TetR-type transcriptional regulator-encoding genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracycline resistance is typically acquired through the activation of efflux pumps ( 18 , 19 ). The family of TetR-type transcriptional regulators is redundantly involved in driving this switching through uncharacterized molecular events ( 3 , 6 ). Strain AB5075 does not possess intrinsic resistance to tetracycline due to the absence of the tetRA cassette ( 20 ), despite having multiple copies of TetR-type transcriptional regulator-encoding genes.…”
Section: Discussionmentioning
confidence: 99%
“…There are 11 structurally related TTTRs identified in the genome of A. baumannii . To inhibit TTTRs associated colony switch drive, the deletion of at least four of these genes is required ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…A phenotypic switch has been described in A. baumannii that generates virulent and avirulent subpopulations ( 40 42 ). Each cell variant can be distinguished by its colony morphology on agar plates using oblique lighting, with virulent variants forming opaque colonies (VIR-O) and avirulent variants forming translucent colonies (AV-T) ( 41 , 43 ). In addition to differences in virulence, the VIR-O variant possesses a thicker capsule than the AV-T variant; it is considerably more motile and secretes greater amounts of the quorum-sensing signal 3-hydroxy-dodecanoyl-l-homoserine lactone (3-OH-C 12 -HSL)( 40 , 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that the stochastic activation of a family of TetR-type transcriptional regulators (TTTRs) is able to drive the cells from the VIR-O state to many of the phenotypes associated with the AV-T state ( 43 ). Activation of the TTTR ABUW_1645 ( ABUW_RS08030 ) constitutes the preferred pathway to switch and it gives rise to avirulent AV-T variants.…”
Section: Introductionmentioning
confidence: 99%
“…Only seven A. baumannii ATCC17978 sRNAs are conserved (between 70-75% sequence identity) across selected members of the Pseudomonadales (e.g., Pseudomonas aeruginosa and Moraxella catarrhalis ) and none shares any sequence conservation with sRNAs in Enterobactericeae (Kröger et al ., 2018). A few sRNAs in A. baumannii have been functionally characterised and were shown to be involved in the regulation of efflux pumps, biofilm formation and phenotypic switching between virulent and avirulent phase variants (Sharma et al ., 2014; Álvarez-Fraga et al ., 2017; Anderson et al ., 2020; Pérez-Varela et al ., 2022; Shenkutie et al ., 2023). However, their direct targets and mechanism of action have not been dissected.…”
Section: Introductionmentioning
confidence: 99%